CONSTRAINED EFFICIENT MARKETS FOR MANIPULATION ECONOMIES - Citanna, Alex; Siconolfi, Paolo (International economic review (Philadelphia), 2020)
We design a competitive market for exclusive contracts in large economies with observable types where trades are subject to postcontractual manipulations. We do not impose quantity restrictions at the trading stage—for example, incentive constraints on the consumption or production sets. We establish existence and constrained optimality of equilibrium. Our design can accommodate manipulations stemming from private information as well as from behavioral biases—for example, time inconsistency and false beliefs. We discuss the needed size and complexity of the commodity set.